Selected Decisions and Selected Documents of the International Monetary Fund. (Selected Decisions; Twenty-Second Issue, 1997, 1997)
This Volume contains decisions, interpretations, and resolutions of the Executive Board and the Board of Governors of the IMF, as well as selected documents relating to current activities of the Fund.